The Role of Media Coverage in Corporate China - WANG, Jiwei (Institutional Knowledge at Singapore Management University, 2012)
We find that Chinese media can still play monitoring role in listed companies although the media is highly controlled by the government. Firms with more media coverage tend to use more effective pay-for-performance compensation packages and are more likely to introduce independent directors and hire good quality auditors. We also document that media coverage can help to prevent the occurrence of financial fraud and firms with more media coverage have higher valuation. Our study complements the emerging literature on the monitoring role of media. Our results also give policy implications to Chinese government and other developing markets.